BIOGAS PRODUCTION USING WASTE WATERS – INFLUENCE OF PROCESS PARAMETERS FOR TEST RIG AT LABORATORY SCALE - CIOABLĂ, Adrian Eugen; DJURIC, Aleksandar; DUMITREL, Gabriela-Alina; CHIRILĂ, Daniel; PODE, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Biogas production by anaerobic digestion of residual waters from different sources (a treatment plant and a beer factory) was investigated in laboratory small scale batch reactors. Both wastewaters represent efficient biogas substrates. As concern the methane composition, the value is slightly higher in the case of biogas produced by anaerobic digestion of wastewater from beer factory. In the second part of this study, anaerobic co-digestion of wastewater and cow whey was performed. Addition of cow whey to wastewater from beer factory increase the biogas yield, while the addition of cow whey to wastewater from treatment plant decrease the biogas yield. In both cases of co-digestion, the methane content in biogas was higher than in the single digestion processes.